THE EFFECT OF PROBLEM BASED LEARNING MODEL WITH SCIENTIFIC LITERACY ON STUDENTS COGNITIVE LEARNING OUTCOMES IN CLASS VII ECOLOGY MATERIAL AT SMP NEGERI 12 MEDAN - Sipahutar, Melati Sri Agnes; Sipahutar, Herbert (Universitas Negeri Medan, 2025)
The Study aims to determine the effect of the problem based learning model with scientific literacy on students cognitive learning outcomes in ecology material. Population in the study were all students of class VII of SMP Negeri 12 Medan consisting of 9 classes with a total of 284 students. The Sample was taken from one class, namely the experimental class VII-2 with a total of 30 students. Type of research is quantitative research with pre experimental and research design used is one group pre-test and post-test design. Data analysis technique used the paired sample t-test hypothesis test using SPSS Statistics 25 software. Average and standard deviation pretest is 39.06 ± 8.77 and the posttest is 86.63 ± 7.22. Results of the hypothesis test obtained results with Sig. value data (2-tailed) of 0.000<0.05, the hypothesis Ha is accepted and H0 is rejected. The conclusion is that the problem based learning model with scientific literacy has an effect on students cogntive learning outcomes in the ecology material of class VII at SMP Negeri 12 Medan.